Kompetensi sosial dan interpersonal faktor utama memperkuat ketahanan diri remaja terhadap penyalahgunaan narkotika di Provinsi Sumatera Selatan - Sari, Yulia Puspita (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Teenager in their mental and social development towards adulthood will definitely be faced with various challenges, one of which is threat of drug abuse. Therefore, teenager must have self-resilience against Narcotics, namely an ability to self control, keep away and refuse all of Narcotics. Until now, efforts to increase self-resilience of teenager against drug abuse in South Sumatra Province have only focused on activities of dissemination P4GN. This thesis aims to analyze each influence factor and the most dominant factor and also analyze the level of self resilience teenager against drug abuse in South Sumatra. This thesis research uses a quantitative approach. The research sample consisted of 100 teenager respondents, they are domiciled in South Sumatra who had received information dissemination from the National Narcotics Agency. The results obtained The most influential factor is social factor and interpersonal competence. That level of self-resilience of teenager against drugs abuse in South Sumatra is included category of moderate self-resilience.